Symbolism of the Sacred Dog: A Mytholinguistic Approach in Kazakh and English - Onalbayeva, A.; Аvakova, R.; Kudyarova, Sh.; Akimisheva, Zh.; Nygmetova, N.; Samenova, S. (Forum for Linguistic Studies, 2025)
The image of a dog holds a special place in the culture and mythology of many peoples. This study examines how the became a sacred symbol associated with the afterworld, ancestral land, and subterranean realms. Using mythological texts, archaeological data, and linguistic analysis, the research identifies unique cultural and universal patterns in stable expressions about dogs in Kazakh and English. The study employs S. Qondybay’s mytholinguistic method and comparative analysis to uncover the sacred and symbolic meanings of these expressions. The findings reveal that the dog is often seen as a guardian of the afterlife and a protector of human souls. The research highlights how specific cultural and linguistic features—unique to certain ethnic groups—are preserved in language. It also demonstrates the continuity of ancient mythological beliefs in modern expressions and rituals. This study contributes to a deeper understanding of the connection between language, culture, and mythology, offering new perspectives for mytholinguistic and cultural research.
Keywords: Sacred Animal; Afterlife; Mythology; Phraseological Analysis; Cultural Symbolism